1975
DOI: 10.1084/jem.142.3.622
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cytotoxic T lymphocytes in vitro. IV. Functional activation of memory cells in the absence of DNA synthesis.

Abstract: The generation of mouse cytolytic T lymphocytes (CTL)' in mixed leukocyte cultures (MLC) is a well characterized model system in which both the afferent and efferent phases ofT-cell-mediated immunity can be studied (1-3). Recently, the potential usefulness of this model has been extended by the demonstration that anamnestic CTL responses can occur under appropriate culture conditions . In particular, re-exposure of long-term MLC cells to the original stimulating alloantigens was found to result in significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Furthermore, CTL generated in the presence of ARA-C wcrc characterized as large cells by vclocitysedimentation cell separation (H. R. MacDonald, and R. K. Lees, unpublished data). Because the functional activation of memory CTL in a secondary response is known to bc independent of DNA synthesis (4,8,16), it could bc argued that the cells in normal splccn which arc stirnulatcd by Con A arc memory CTL resulting from immunization with cross-rcacting environmental antigens. This would seem unlikely, however, because no PHA-dcpendcnt cytolytic activity was observed either in fresh spleen cells or after 24-h culture in the presence of Con A.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CTL generated in the presence of ARA-C wcrc characterized as large cells by vclocitysedimentation cell separation (H. R. MacDonald, and R. K. Lees, unpublished data). Because the functional activation of memory CTL in a secondary response is known to bc independent of DNA synthesis (4,8,16), it could bc argued that the cells in normal splccn which arc stirnulatcd by Con A arc memory CTL resulting from immunization with cross-rcacting environmental antigens. This would seem unlikely, however, because no PHA-dcpendcnt cytolytic activity was observed either in fresh spleen cells or after 24-h culture in the presence of Con A.…”
Section: Discussionmentioning
confidence: 99%
“…Since this induction is polyclonal, a large proportion of T cells should be activated, abrogating the need for clonal expansion required in an antigendependent clonally restricted response. A similar situation exists in the secondary CML response where cytotoxic cells are rapidly induced in the absence of DNA synthesis (27).…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported that DNA synthesis is required for the generation of cytotoxic cells by alloantigens or mitogens (8-10). In contrast, there is at least one report of cytotoxic cell activation independent of DNA synthesis (26,27). To determine whether DNA synthesis accompanied poly A:U activation of cytotoxic cells, normal A/sn or CBA spleen cells were activated by poly A:U (100/~g/ml) during a 2 h incubation at 37°C.…”
mentioning
confidence: 99%
“…CMC (1) by its quicker CD ur ~i m as susuumlul u x s \R = L A iv , * iiviii IV down to 6 x lo4). The effector cells generated in these cultures were then tested for cytotoxic activity at an E:T ratio of 50:l against either Eb or ESb tumor target development (Engers and MacDonald, 1976), (2) by the fact that it does not require proliferation (MacDonald et al, 1975), and (3) by the less stringent requirements of antigen presentation for lymphocyte activation (Wagner et ul., 1976). In the present study we have made use of the high cytotoxic activity of a sec.…”
Section: Discussionmentioning
confidence: 99%